PERFORMANCE COMPARISON OF USART COMMUNICATION BETWEEN REAL TIME OPERATING SYSTEM (RTOS) AND NATIVE INTERRUPT - Novian Habibie; Machmud Roby Alhamidi; Dwi Marhaendro Jati Purnomo; Muhammad Febrian Rachmadi (Faculty of Computer Science - Universitas Indonesia, 2016)
Comunication between microcontrollers is one of the crucial point in embedded sytems. On the other hand, embedded system must be able to run many parallel task simultaneously. To handle this, we need a reliabe system that can do a multitasking without decreasing every task’s performance. The most widely used methods for multitasking in embedded systems are using Interrupt Service Routine (ISR) or using Real Time Operating System (RTOS). This research compared perfomance of USART communication on system with RTOS to a system that use interrupt. Experiments run on two identical development board XMega A3BU-Xplained which used intenal sensor (light and temperature) and used servo as external component. Perfomance comparison done by counting ping time (elapsing time to transmit data and get a reply as a mark that data has been received) and compare it. This experiments divided into two scenarios: (1) system loaded with many tasks, (2) system loaded with few tasks. Result of the experiments show that communication will be faster if system only loaded with few tasks. System with RTOS has won from interrupt in case (1), but lose to interrupt in case (2).